Highly transmissible cytoplasmic incompatibility by the extracellular insect symbiont Spiroplasma - Pollmann, Marie; Moore, Logan D.; Krimmer, Elena; D'Alvise, Paul; Hasselmann, Martin; Perlman, Steve J.; Ballinger, Matthew J.; Steidle, Johannes L.M.; Gottlieb, Yuval (iScience, 2022)
Cytoplasmic incompatibility (CI) is a form of reproductive manipulation caused by maternally inherited endosymbionts infecting arthropods, like Wolbachia, whereby matings between infected males and uninfected females produce few or no offspring. We report the discovery of a new CI symbiont, a strain of Spiroplasma causing CI in the parasitoid wasp Lariophagus distinguendus. Its extracellular occurrence enabled us to establish CI in uninfected adult insects by transferring Spiroplasma-infected hemolymph. We sequenced the CI-Spiroplasma genome and did not find any homologues of any of the cif genes discovered to cause CI in Wolbachia, suggesting independent evolution of CI. Instead, the genome contains other potential CI-causing candidate genes, such as homologues of high-mobility group (HMG) box proteins that are crucial in eukaryotic development but rare in bacterial genomes. Spiroplasma’s extracellular nature and broad host range encompassing medically and agriculturally important arthropods make it a promising tool to study CI and its applications. [Display omitted] •A Spiroplasma strain induces cytoplasmic incompatibility (CI) in a parasitoid wasp•Spiroplasma and CI are efficiently transferred to naive hosts by hemolymph injection•The CI-Spiroplasma genome contains potential CI-causing genes, but no Wolbachia cifs•Absence of cif genes in the Spiroplasma genome suggests an independent origin of CI Zoology; Entomology; Microbiology; Microbiology parasite